WIP1 phosphatase as pharmacological target in cancer therapy - Pecháčková, Soňa; Burdová, Kamila; Macurek, Libor (Journal of molecular medicine, 2017)
DNA damage response (DDR) pathway protects cells from genome instability and prevents cancer development. Tumor suppressor p53 is a key molecule that interconnects DDR, cell cycle checkpoints, and cell fate decisions in the presence of genotoxic stress. Inactivating mutations in TP53 and other genes implicated in DDR potentiate cancer development and also influence the sensitivity of cancer cells to treatment. Protein phosphatase 2C delta (referred to as WIP1) is a negative regulator of DDR and has been proposed as potential pharmaceutical target. Until recently, exploitation of WIP1 inhibition for suppression of cancer cell growth was compromised by the lack of selective small-molecule inhibitors effective at cellular and organismal levels. Here, we review recent advances in development of WIP1 inhibitors and discuss their potential use in cancer treatment.
Keywords: Antineoplastic Agents; Neoplasms; proteinfosfatasa 2C; protinádorové látky; lidé; nádorový supresorový protein p53; konformace proteinů; Oncogenes; Tumor Suppressor Protein p53; Animals; DNA Damage; onkogeny; poškození DNA; zvířata; Humans; Protein Conformation; nádory; Protein Phosphatase 2C